Against Loveless Judging: Fritz Bauer and Transitional Justice in Postwar Germany. (17th November 2017) - Chung, C K Martin
Abstract ∞ : Fritz Bauer (1903–1968) is a key actor in postwar (West) Germany's arduous transitional justice process. His remembrance is embroiled in controversies of late due to his multiple minority identities as depicted in a number of recent academic works and cultural representations about his life. This article examines Bauer's original writings and speeches to deduce a neglected aspect of his 'intersectionality' – his conception of judicial reform based on his interpretation of biblical and theological sources. It proposes that 'loveful judging, ' or judging with love, as derived from his critique against the 'loveless judging' during the Nazi era, is a fitting encapsulation of Bauer's thoughts on issues of punishment, resistance, reparation and resocialization. As such, the concept is useful both as an internal standard to evaluate Bauer's achievements, and as a unique contribution, based on the West German context, to the wider discussion on retributive and restorative justice.